Peran Digitalisasi Zakat dalam Peningkatan Fundraising dan Jumlah Muzakki di Indonesia - Muhammad Rizaludin As (Tadabbur: Jurnal Integrasi Keilmuan, 2022)
Zakat is a sharia economic instrument that has a role not only from the religious dimension but also in the social dimension. One of the roles of zakat is to overcome poverty by distributing wealth evenly from muzakki to mustahik. This can be done by optimizing the potential of zakat, one of which is through digitalizing zakat. The purpose of this study is to determine the extent to which the role of digitizing zakat in increasing fundraising and the number of muzakki in Indonesia and how digitizing zakat has a major impact on the development of zakat. The research method used is descriptive qualitative. The results of this study indicate that most people choose to pay zakat using fintech, for example through instant payment or via transfer from m-banking which makes it easier for them, so it can be concluded that the effect of digitizing zakat is able to facilitate and increase fundraising and the number of muzakki in Indonesia.